BRIDGING THEORY AND LEARNING: PEDAGOGICAL CHALLENGES IN AN EFL PSYCHOLINGUISTICS COURSE - Indahyanti, Rizka; Rahman, Ali Wira (Lembaga Jurnal FKIP Universitas Bosowa, 2025)
Psycholinguistics is a core theoretical course in English Language Teaching (ELT) programmes, yet it is often perceived as challenging by EFL undergraduates due to its abstract concepts and cognitive demands. This study explores pedagogical challenges in bridging psycholinguistic theory and student learning in an EFL higher education context. Adopting a classroom-based qualitative case study design, the research was conducted in an undergraduate psycholinguistics course within an English education programme. Data were collected through classroom observations, student reflective journals, focus group discussions, and document analysis. Thematic analysis revealed several key challenges, including the abstract nature of theoretical concepts, difficulties in mediating theory through pedagogical practices, reduced student engagement during explanation-dominated instruction, and the linguistic demands of learning theory in English. The findings highlight the central role of pedagogical mediation in supporting students’ conceptual understanding and engagement in theory-oriented courses. Rather than viewing students’ difficulties as individual deficits, the study underscores the importance of examining pedagogy as a situated and relational practice shaped by teacher cognition and classroom context. The study offers pedagogical implications for EFL lecturers and teacher education programmes seeking to make psycholinguistics and other theory-based courses more accessible and meaningful for undergraduate learners